2016
DOI: 10.1016/j.jspi.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imputation in three or more stages

Abstract: Missing values present challenges in the analysis of data across many areas of research. Handling incomplete data incorrectly can lead to bias, over-confident intervals, and inaccurate inferences. One principled method of handling incomplete data is multiple imputation. This article considers incomplete data in which values are missing for three or more qualitatively different reasons and applies a modified multiple imputation framework in the analysis of that data. Included are a proof of the methodology used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The largest amount of missing data in this study was associated with ethnic identity (10%). Although various missing data techniques are available (McGinniss & Harel, ), missing data were handled using maximum likelihood (ML) estimations through AMOS (version 23.0) software, which addresses the missing data and parameter estimates, and estimates the standard error in a single step (Hancock & Liu, ). Using AMOS to handle missing data also allows for a theoretically informed direct approach to handling missing data through modeling, opposed to other imputation methods, which can be designated as indirect (Byrne, ).…”
Section: Methodsmentioning
confidence: 99%
“…The largest amount of missing data in this study was associated with ethnic identity (10%). Although various missing data techniques are available (McGinniss & Harel, ), missing data were handled using maximum likelihood (ML) estimations through AMOS (version 23.0) software, which addresses the missing data and parameter estimates, and estimates the standard error in a single step (Hancock & Liu, ). Using AMOS to handle missing data also allows for a theoretically informed direct approach to handling missing data through modeling, opposed to other imputation methods, which can be designated as indirect (Byrne, ).…”
Section: Methodsmentioning
confidence: 99%
“…Further inspection of these data revealed that the largest amounts of missing data were related to school importance (< 10%). Although, numerous missing data techniques are available (McGinniss & Harel, ), missing data for this study were handled using maximum likelihood through IBM SPSS AMOS (v. 25), a structural equation modeling software.…”
Section: Methodsmentioning
confidence: 99%
“…Further inspection of data revealed that no more than 5% of data were missing for any given variable. Although numerous missing data techniques are available (McGinniss & Harel, ), missing data for this study were handled using maximum likelihood (ML) through AMOS SEM software.…”
Section: Methodsmentioning
confidence: 99%